Development of community participation indicators to advance the quality of spinal cord injury rehabilitation: SCI-High Project. (30th September 2021) - Hitzig, Sander L.; Jeyathevan, Gaya; Farahani, Farnoosh; Noonan, Vanessa K.; Linassi, Gary; Routhier, François; Jetha, Arif; McCauley, Diana; Alavinia, S. Mohammad; Omidvar, Maryam; Craven, B. Catharine
Abstract : Context : Community participation following spinal cord injury/disease (SCI/D) can be challenging due to associated primary impairments and secondary health conditions as well as difficulties navigating both the built and social-emotional environment. To improve the quality of SCI/D rehabilitation care to optimize community participation, the SCI-High Project developed a set of structure, process and outcome indicators for adults with SCI/D in the first 18 months after rehabilitation admission. Methods : A pan-Canadian Working Group of diverse stakeholders: (1) defined the community participation construct; (2) conducted a systematic review of available outcomes and their psychometric properties; (3) constructed a Driver diagram summarizing available evidence associated with community participation; and (4) prepared a process map. Facilitated meetings allowed selection and review of a set of structure, process and outcome indicators. Results : The structure indicator is the proportion of SCI/D rehabilitation programs with availability of transition living setting/independent living unit. The process indicators are the proportion of SCI/D rehabilitation inpatients who experienced: (a) a therapeutic community outing prior to rehabilitation discharge; and, (b) those who received a pass to go home for the weekend. The intermediary and final outcome measures are the Moorong Self-Efficacy Scale and the Reintegration to Normal Living Index. Conclusion : The proposed indicators have the potential to inform whether inpatient rehabilitation for persons with SCI/D can improve self-efficacy and lead to high levels of community participation post-rehabilitation discharge.